How Robust Is Indonesia's Poverty Profile? Adjusting for Differences in Needs. Issue 2 (3rd May 2016) - Priebe, Jan
Abstract : Poverty profiles showing how the magnitude of poverty differs across subgroups of a population are important tools in designing effective social protection programs. Using data from the March 2013 round of the National Socio-economic Survey (Susenas) and the fourth round of the Indonesia Family Life Survey (2007–8), I explore the sensitivity of Indonesia's poverty profile to different assumptions about the relative costs of individuals, taking into account differences in age, gender, body weight, and physical activity levels. I adopt parameter estimates for my simulation exercises from various Indonesia-specific publications, as well as from a joint intergovernmental consultation on nutrition. I compare my estimates with the per capita scale used by Statistics Indonesia (BPS), the central statistics agency. My findings suggest that the age–poverty relationship in Indonesia is sensitive to assumptions about the relative costs of individuals, with all alternative scales showing substantially lower poverty incidence among young children than by BPS's estimate. Overall, however, I find that Indonesia's poverty profile is relatively robust.